Pritisk na fundus med drugo porodno dobo - Štinek, Jerneja (Obzornik zdravstvene nege, 2013)
Introduction: Though the role of fundal pressure is still understudied and remains controversial, it is frequently used as an obstetric technique to assist spontaneous vaginal delivery and avoid prolonged second stage of labour. The purpose of the article is to identify the prone factors of the useof uterine fundal pressure maneuver and to evaluate its obstetrical outcomes. Methods: The literature review and meta-synthesis of scientific studies were performed using the COBIB.SI and databases of Medline, CINAHL, ScienceDirect, PubMed, Cochrane Collaboration, Wiley Online Library in Springer Link with the following keywords and phrases: fundal pressure, second stage of labour, shoulder dystocia, uterine rupture. 152 pertinent articles were found and seven studies were analysed. Included in the review were the papers published from 1996 till 2011, with the entire text available online, either in English or Slovene. All the texts were related to the effectiveness and safety of the manoeuvre. The studies were evaluated and analysed for their methodological quality and on the basis of the sample, research parameters and results. Results: There is little evidence to demonstrate that the use of fundal pressure is effective to improve maternal and/or neonatal outcomes. Moreover, there may be some adverse maternal/fetal effects, such as brachial plexus injuries (the baby), rupture of uterus or broken ribs (the mother) and increased possibility of serious perineal ruptures. There is also a scarcity of literature substantiating that fundal pressure dicreases the duration of the second stage of labour. Discussion and conclusion: It is commendable that accurate and thorough documentation be kept of all the manouvers performed in Slovenian hospitals. It is necessary to determine the incidence rate of the manouver and evaluate its effect on maternal and neonatal outcomes and whether fundal pressure benefits counterbalance the harms. Evidence-based clinical practice guidelines could thus be developed for future practice and midwives' responsibility.
Keywords: active management; aktivno vodenje; childbirth; druga porodna doba; fundal pressure; intrapartum injuries; length of expulsion; midwife's role; porod; porodne poškodbe; pritisk na fundus; second stage of labour; trajanje iztisa ploda; vloga babice